Precision feeding approach affecting growth, nutrient utilization, feed conversion efficiency and economics of feeding weaned Murrah buffalo calves - MUDGAL, VISHAL; SAXENA, NAVNEET; MOHAN, CHANDER; JAIN, SHIKHA; KUMAR, KRISHNA; SHARMA, MADAN LAL; KUMAR, RAJESH (The Indian Journal of Animal Sciences, 2018)
The biological value of protein affects the growth of pre-ruminant calves and most deficient (critical) amino acids are methionine and lysine, which have an important role to play in balancing of amino acids for efficient utilization of feed protein (CP). Planning was made to develop economical calf starter for weaned buffalo (Bubalus bubalis) calves. Equal-energy calf starters (CS) were prepared with variable protein and amino acid levels, CS1 for control group (26% CP) was made with natural feed ingredients only, while designer CSs for groups CS2 and CS3, had 2 levels of critical amino acids with reduced CP content (21 and 20%, respectively) and fed to 3 groups of 6 calves (age 30 to 45 days and 58.40 kg mean body weight) each for 3 months. Higher growth rate and savings on the cost of feed per kg weight gain was achieved without affecting the digestibility of organic nutrients.